The Role of Effective Human Resource Management: Case Study of Start Up Cool Kids at Ambon City Centre Mall - Bernard C. Renyut; Semuel Willem Sipahelut; Pulina Wakanubun (Innovation Business Management and Accounting Journal, 2022)
This study aims to describe the application of Human Resource Management (HRM) in recruiting employees to improve performance, analysis of HRM in efforts to develop human resources to improve employee performance, HRM analysis has an impact on recruitment and efforts in HR development to improve employee performance in the start-up sector Cool Kids at Ambon City Centre Mall. This study uses a descriptive qualitative approach. This research approach was carried out at Cool Kids in Ambon City Centre Mall with data collection techniques in the form of interviews, observation, documentation and accommodation methods. The results of this study are expected that the recruitment system carried out is not fully maximized, so using the human resource management recruitment model can be carried out effectively. In an effort to develop of human resources, this has been carried out in accordance with the procedures for implementing employee education and training programs, but this has not yet been implemented informally. HR development and recruitment have an impact on improving employee performance which has not been fully implemented, this is due to the knowledge, abilities and skills of employees not all of them can master them effectively.